Development of Audio-Visual Physics Animation Media to Improve Students’ Understanding of Concepts and Creativity - Fita Permata Sari; Salamun Hadi Subroto; Faruq Haroky (Jurnal Penelitian & Pengembangan Pendidikan Fisika, 2022)
Increasing technology in this modern era of globalization can be applied to the world of education as a facility to facilitate the learning process delivered. Applying technology can help to learn that are hampered by distance can be overcome by distance learning. Distance learning has not yet become a part of most schools in Indonesia, especially elementary schools. So, there is a need for further research to produce audio-visual animation media so that it can help to learn for elementary school students. This type of research is an educational R&D development research (Educational Research and Development) referring to the ADDIE development model, which consists of five stages: Analyze, Design, Development, Implementation, and Evaluation. The type of data used is descriptive qualitative and quantitative data. Techniques for data collection are using questionnaires and questions. This shows no difference between using audio-visual animation learning media for science-themed to permanently save energy and other media provided by educators in schools to improve students’ conceptual understanding and creativity.